2016
DOI: 10.21831/cp.v1i1.8365
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Game Petualangan “Si Bolang” Sebagai Media Pembelajaran Tematik Untuk Meningkatkan Motivasi Dan Prestasi Belajar Siswa Kelas v Sekolah Dasar

Abstract: Abstrak: Tujuan Penelitian ini untuk mengetahui pengembangan media pembelajaran berbasis game yang menarik dan mengetahui perbedaan motivasi dan prestasi belajar dengan media tersebut. Metode penelitian yang digunakan adalah penelitian pengembangan. Hasil pengembangan divalidasi oleh pakar media dan IT, sedangkan validasi materi dan tes evaluasi game dilakukan oleh ahli materi bahasa indonesia dan PKn. Instrumen pengumpulan data yang dipakai adalah angket dan tes. Teknik analisis data yang digunakan adalah tek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
13

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 3 publications
0
11
0
13
Order By: Relevance
“…Multimedia learning is very liked by students (Khamparia & Pandey, 2017;Majid et al, 2012). The game-based learning media is very interesting for students (Bartel & Hagel, 2014;Emerson et al, 2020;Sunarti et al, 2016). The educational games can increase student's attention, concentration and improve student learning outcomes (Kao, 2020;Su & Cheng, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Multimedia learning is very liked by students (Khamparia & Pandey, 2017;Majid et al, 2012). The game-based learning media is very interesting for students (Bartel & Hagel, 2014;Emerson et al, 2020;Sunarti et al, 2016). The educational games can increase student's attention, concentration and improve student learning outcomes (Kao, 2020;Su & Cheng, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another study that is relevant to the present findings is that of Sunarti et al (2016). Their findings show that there is a difference in the learning motivation between students who are taught using games and visual media and those who are taught using conventional media.…”
Section: Media Use In the Implementationmentioning
confidence: 62%
“…In another study, it is shown that language learning using Facebook can increase learners' self-confidence and motivation (Kabilan & Zahar, 2016). Still from another study, it is shown that good use of instructional media contributes significantly to the improvement of learners' motivation and teachers' and learners' active participation (Nugrahani, 2017) and (Sunarti, 2016). Meanwhile, the use of effective media can be appraised by its impacts whether or not it can differentiate superior schools from inferior ones and effective teachers from less effective ones (Oyedele et al, 2013).…”
Section: Media Use In the Implementationmentioning
confidence: 99%
“…Berbagai macam media pembelajaran tersebut berfungsi untuk menarik minat siswa, agar dapat mengikuti proses belajar dengan baik. Briggs dalam Sudrajat (2008) menyatakan bahwa media pembelajaran merupakan salah satu cara atau alat bantu yang digunakan dalam proses belajar mengajar. Media pembelajaran adalah sarana fisik untuk menyampaikan isi atau materi pembelajaran seperti: buku, film, video dan sebagainya.…”
Section: Diterimaunclassified